REDUCTION OF ROTATION SPEED OF ELECTRIC DRIVE ELECTRIC MOTORS - Abdusalyamova , Tillokhon (Educational Research in Universal Sciences, 2023)
The calibration parameters introduced in the MATLAB program above allowed us to determine the values of p, v, and w for the confidence gradient value. Taking into account the malfunctions of electric drives, the decrease in the rotation speed of electric motors, vibration and noise in the electric motor, the factors of short-term changes in their rotation speed, the tested motor is provided with a frequency converter in the fs=10-50 Hz range, under the control of us/fs=const works at open speed